A Possible Anticancer Agent, Type III Interferon, Activates Cell Death Pathways and Produces Antitumor Effects - Masatoshi Tagawa; Kiyoko Kawamura; Quanhai Li; Yuji Tada; Kenzo Hiroshima; Hideaki Shimada (Clinical and Developmental Immunology)
Recently identified interleukin-28 and -29 belong to a novel type III interferon (IFN) family, which could have distinct biological properties from type I and II IFNs. Type I IFNs, IFN-α/β, have been clinically applied for treating a certain kind of malignancies for over 30 years, but a wide range of the adverse effects hampered the further clinical applications. Type III IFNs, IFN-λs, have similar signaling pathways as IFN-α/β and inhibits proliferation of tumor cells through cell cycle arrest or apoptosis. Restricted patterns of type III IFN receptor expression in contrast to ubiquitously expressed IFN-α/β receptors suggest that type III IFNs have limited cytotoxicity to normal cells and can be a possible anticancer agent. In this paper, we summarize the current knowledge on the IFN-λs-mediated tumor cell death and discuss the functional difference between type I and III IFNs.